Neonatal Group B Streptococcal Infection in Australia: A Case–control Study. Issue 5 (16th March 2023) - Yanni, Marianne; Stark, Michael; Francis, Laura; Francis, Joshua R.; McMillan, Mark; Baird, Rob; Heath, Paul T.; Gordon, Alex; Riccardione, James; Wilson, Angela; Lee, Rebecca; Chooi, Kathrina; et al.
Abstract : Background: To determine maternal and neonatal risk factors for, and incidence of, neonatal early-onset group B streptococcus (EOGBS) and late-onset (LOGBS) infection in South Australia (SA) and the Northern Territory (NT). Methods: A case–control study with 2:1 matched controls to cases. The study included tertiary hospitals in South Australia and the Northern Territory, Australia. Retrospective data were collected from a 16-year epoch (2000–2015). Results: Of a total of 188 clinically suspected or confirmed cases, 139 were confirmed, of which 56.1% (n = 78) were EOGBS and 43.9% (n = 61) were LOGBS. The incidence of clinically suspected and confirmed cases of EOGBS was 0.26/1000 live births in SA and 0.73/1000 live births in the NT, and the incidence of confirmed cases was 0.19/1000 for SA and 0.36/1000 for the NT. The incidence of clinically suspected or confirmed LOGBS was 0.18/1000 live births in SA and 0.16/1000 for the NT. The majority of infants with GBS presented with sepsis, pneumonia, or meningitis. Developmental delay was the most commonly recorded long-term complication at 1 year old. Risk factors for EOGBS included maternal GBS carriage, previous fetal death, identifying as Aboriginal and/or Torres Strait Islander, and maternal fever in labor/chorioamnionitis. Conclusions: GBS remains a leading cause of neonatal morbidity and mortality. Adding previous fetal death to GBS screening guidelines would improve GBS prevention. The introduction of maternal GBS vaccination programs should be guided by country-specific disease epidemiology.